Frontispiece: In Vivo Subcellular Mass Spectrometry Enables Proteo‐Metabolomic Single‐Cell Systems Biology in a Chordate Embryo Developing to a Normally Behaving Tadpole (X. laevis). Issue 23 (26th May 2021) - Lombard‐Banek, Camille; Li, Jie; Portero, Erika P.; Onjiko, Rosemary M.; Singer, Chase D.; Plotnick, David O.; Al Shabeeb, Reem Q.; Nemes, Peter
Abstract : Bioanalytics Single‐cell mass spectrometry was advanced by Peter Nemes et al. in their Research Article on page 12852 to enable dual characterization of proteins and metabolites in embryo cells.